Robustness of Subjective Welfare Analysis in a Poor Developing Country: Madagascar 2001 - Lokshin, Michael; Umapathi, Nithin; Paternostro, Stefano (World Bank, Washington, D.C., 2013)
The authors analyze the subjective perceptions of poverty in Madagascar in 2001 and their relationship to objective poverty indicators. They base their analysis on survey responses to a series of subjective perception questions. The authors extend the existing empirical methodology for estimating subjective poverty lines on the basis of categorical consumption adequacy questions. Based on this methodology they calculate the household-specific, subjective poverty lines and compare the poverty profiles derived from different subjective welfare questions. The results show that the aggregate poverty measures derived from consumption adequacy questions accord quite well with the poverty measures based on objective poverty lines. The subjective welfare analysis can be used in poor developing countries for evaluating socioeconomic and distributional impacts of various policy interventions.